Let's celebrate recovery. Inclusive Cities working together to support social cohesion. (2nd January 2019) - Best, David; Colman, Charlotte
Abstract: Recovery from illicit drug and alcohol use takes place over time and is characterised by a dynamic interaction between internal and external components. An integral part of all recovery journeys is effective community reintegration. After all, recovery is not mainly an issue of personal motivation rather it is about acceptance by family, by friends and by a range of organisations and professionals across the community. Therefore to support pathways to recovery, structural and contextual endeavours are needed to supplement individually-oriented interventions and programmes. One way to do this, is by introducing Inclusive Cities. An Inclusive City promotes participation, inclusion, full and equal citizenship to all her citizens, including those in recovery, based on the idea of community capital. The aim of building recovery capital at a community level through connections and 'linking social capital' to challenge stigmatisation and exclusion, is seen as central to this idea. Inclusive Cities is an initiative to support the creation of Recovery-Oriented Systems of Care at a city level, that starts with but extends beyond substance using populations. This paper describes (and gives examples of) how it is possible to use recovery as a starting point for generating social inclusion, challenging the marginalisation of other excluded populations as well by building community connections.